A literature review on flow‐rate variability in neonatal IV therapy. Issue 1 (12th October 2012) - van der Eijk, Anne C.; van Rens, Roland M.F.P.T.; Dankelman, Jenny; Smit, Bert J.; Hammer, Greg
Summary Aim To provide an overview of factors influencing the flow rate in intravenous (IV) therapy for newborns. Methods We conducted a review of the literature from 1980 to 2011 in PubMed and Web of Knowledge. Articles focusing on flow‐rate variability and possible complications due to flow‐rate variability were included. Results Forty‐one articles were selected for this review. IV therapy in (preterm) neonates is prone to significant start‐up delays and flow‐rate variability. The sudden changes in the volume delivered to (preterm) neonates may have serious consequences. Low preprogrammed flow rates, total compliance, and volume of the IV administration set, the presence or absence of antisiphon valves or inline filters and the vertical displacement of syringe pumps all contribute to flow‐rate variability in IV therapy for neonates. Conclusions Flow‐rate variability in IV therapy and its clinical relevance are due to the preprogrammed flow rate, the hydrostatic pressure changes, the complete IV administration set compliance and the type of substances supplied to the patient. To improve IV therapy, the internal compliance of the complete IV administration set should be minimized and the highest possible preprogrammed flow rate should be used in combination with small syringes and low‐resistance valves.